Method for producing carbonized mineral component, carbonized mineral component and method for producing hydraulic binder
By subjecting concrete waste to low-temperature heat treatment and carbonization, carbonized mineral components with pozzolanic reactivity are prepared, solving the problems of strength loss and high carbon footprint in existing technologies, and realizing a cement-concrete composite with high strength and low carbon footprint.
Patent Information
- Application Number
- CN202380040939.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-21
- Filing Date
- 2023-04-21
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, carbonized concrete waste cannot effectively improve strength when used as a mineral component in cement and concrete composites, and the carbonization process may lead to strength loss, and the carbon footprint of the carbonization process is high.
By subjecting concrete waste to low-temperature heat treatment and carbonization, and combining this with the use of sustainable energy, carbonized mineral components with pozzolanic reactivity are prepared and used as a substitute for hydraulic binder compositions, particularly cement.
Without sacrificing strength, it significantly improves the mechanical strength of cement and concrete and effectively captures CO2, reducing the carbon footprint.
Smart Images

Figure HDA0005137020800000011 
Figure HDA0005137020800000012 
Figure HDA0005137020800000013
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbonized mineral component, a carbonized mineral component and a method for preparing a hydraulic binder composition. Background Art
[0002] Carbonization of materials used for building materials is well known. Examples include the carbonization of steel slag, special cement and concrete construction waste. The known carbonization of materials can be divided into two main methods.
[0003] The first method is to harden the material by carbonization. The carbonization method is well known for hardening and uses standard processes. For example, this method is disclosed in patent applications filed by Carbstone Innovation, Solidia Technologies or CarbonCure.
[0004] The methods disclosed in these applications have the advantage of sequestering CO2 by forming calcium carbonate particles. This can be achieved in a variety of construction applications, such as the production of small building elements such as paving bricks or blocks. In these methods, the material to be carbonized can be mixed with a small amount of water and placed in a mold. These molds are then placed in a curing chamber with a relatively high CO2 content and controlled temperature and relative humidity. Through the carbonization of the material, the carbonized element has enhanced mechanical strength.
[0005] The second method is to carbonize a mineral component and then use it in powder form as a carbonized mineral component. The purpose is to reduce the amount of Portland cement clinker in a cement composite by replacing part of the Portland cement with this powder made of the carbonized mineral component. In the method according to the second method, a carbonized mineral material is used in a specific form and then added to the Portland cement clinker as a cement substitute. For example, construction waste is carbonized by different processes and the resulting product is used as a cement substitute. Therefore, in order to provide a material with a reduced CO2 footprint, the amount of Portland cement clinker in cement is reduced. In the second method, as mentioned above, carbonization leads to the formation of calcium carbonate particles, which are used as a filler material but do not contribute to the strength development of cement. Therefore, the higher the carbonization rate of concrete construction waste, in principle, it will lead to lower strength development. In fact, the amount of the carbonized mineral component according to the second method is limited in the cement composite. The second method is disclosed, for example, in EP 3656750, WO 2019 / 115722, EP 3581257 and EP 3498681 A1.
[0006] Yingpeng Hu, Journal of Energy Chemistry, Vol. 26, No. 5, September 2017, pp. 927-935 It is known to use (NH4)2SO4 as a recoverable extractant for indirect mineral carbonization of blast furnace slag, wherein in this document, CO2 is fixed by low-temperature roasting with aqueous carbonization, and (NH4)2SO4 is used to extract calcium and magnesium from blast furnace slag (the main phases of gehlenite and akermanite).
[0007] Daniela Angulo, Materials de Construccion 69(333):182 deals with the carbonation of high-slag concrete and its effect on the corrosion of structural steel.
[0008] Junho Kim, Seung Hyun Na and Yukio Hama, Materials (Basel), 2020, November 13, (21): 4787, disclosed the effects of blast furnace slag substitution rate and curing method on the pore structure changes of cement paste after carbonization.
[0009] “Comparison of CO2 emissions from OPC and recycled cement production”, Zhijun He; Xiaodong Zhu, Junjie Wang, Mulan Mud, Yuli Wang; Construction and Building Materials, Vol. 211, June 30, 2019, pp. 965-973 discloses that the production of ordinary Portland cement (OPC) accounts for a large part of global CO2 emissions. In order to reduce CO2 emissions in cement production, two types of recycled cement (RC-450℃ and RC-800℃) were produced in this study. The application of recycled cement can significantly reduce the environmental impact caused by landfill of construction concrete waste. Recycled cements RC-450℃ and RC-800℃ are produced by burning old OPC slurry at 450℃ and 800℃, respectively, and then grinding it into powder with a ball mill. By considering the CO2 emissions of fuel combustion and clinker, the CO2 emissions of producing OPC, RC-450℃ and RC-800℃ were calculated and compared. The production of RC-450℃ reduces CO2 emissions by 94% compared to the production process of OPC. By mixing with water, an additional 4% of the CO2 by weight of RC-450℃ can be captured in the RC-450℃ slurry through the formation of calcium carbon aluminate and other calcites. Compared with RC-800℃, RC-450℃ has lower CO2 emissions but higher slurry strength. In addition, RC-450℃ slurry was found to have similar strength to OPC slurry, indicating that RC-450℃ can completely replace OPC.
[0010] From "Recycled cement"; Junjie Wang, Mulan Mu, Yongliang Liu, Construction and Building Materials, Vol. 190, November 30, 2018, pp. 1124-1132, it can be seen that cement recycling can reduce the environmental impact caused by waste concrete landfill and the demand for raw materials for cement production, because the waste cement slurry in waste concrete can be used to produce recycled cement. Recycled cement is produced by burning waste cement slurry for 2 years at 4 different temperatures (120℃, 450℃, 750℃ and 1150℃) and then grinding it into powder. The selected temperature is the temperature at which significant weight loss occurs based on the thermogravimetric analysis (TGA) results of the old cement slurry. The results show that the compressive strength reaches the highest at 450℃, and the strength of the recycled cement slurry is similar to that of the OPC slurry, but the workability is poor, even beyond the measurement range of the rheometer. Increasing the particle size of recycled cement powder and partially replacing cement powder with ground granulated blast furnace slag (GGBS) can effectively improve the workability of recycled cement paste without reducing the compressive strength.
[0011] Paper "CO2 mineralization of demolished concrete wastes into asupplementary cementitious material-a new CCU approach for the cementindustry", Maciej Zajac, Global R&D, Jan Skocek, Skibsted, Mohsen Ben Hahain RILEM Technical Letters, Open Access Journal of RILEM, RILEM Tech Lett, ISSN 2518-0231, Vol. 6, 2021, presents the carbon capture and utilization (CCU) method based on CO2 mineralization of cement paste in recycled concrete as a new method to capture CO2 and contribute to a significant reduction in CO2 emissions associated with cement production. It points out that the current literature shows that all CO2 released by the decomposition of limestone during clinker production can be sequestered by carbonization of scrap cement paste. This carbonization can be completed within a few hours at ambient temperature and pressure and at relatively low CO2 concentrations in the gas (<10%). The carbonization of cement paste produces calcite and amorphous alumina-silica gel, the latter being a pozzolanic material that can be used as a supplementary cementitious material. Due to its high specific surface area and amorphous structure, alumina-silica gel has a very rapid pozzolanic reaction. Therefore, composite cements containing carbonized cement paste have the characteristics of rapid strength increase. The successful implementation of this CCU approach also relies on improved concrete recycling technologies and methods currently being developed to separate fines from cement paste. Total concrete recycling will further improve the recycling rate of cement and concrete by using recycled aggregates instead of natural sedimentation of aggregates. Although the feasibility of this process has been demonstrated on an industrial scale, several unanswered questions related to the optimal carbonation conditions and the properties of the carbonized material remain in the new composite cements.
[0012] From the article “Carbon Capture and Utilization by mineralization of cementpastes derived from recycled concrete, Jan Skocek et al. Scientific reports, Vol. 10, No. 1, March 27, 2020, pp. 5614-1, ISSN: 2045-2322, it is known that fines can be produced from recycled concrete and subjected to a carbonization step in an autoclave using a pure CO2 atmosphere at pressures between 1 and 8 bars and temperatures between 20 and 200°C.
[0013] JP 2005 320202A discloses a method for preparing a cement composition using waste concrete fine powder, wherein powders of hardened cement paste and aggregates, which have been carbonized to a certain extent during initial use, are dehydrated by a heating device within a specified temperature range of 300°C to 500°C. Summary of the invention
[0014] The object of the present invention is to provide a method for preparing a carbonized mineral component which, when added to a hydraulic binder composition as a replacement for a hydraulic component, in particular cement, does not result in a loss of strength.
[0015] This object is achieved by a method according to claim 1 .
[0016] Another object of the present invention is to provide a carbonized mineral component as a substitute for the hydraulic component in the hydraulic binder composition.
[0017] This object is achieved by a carbonized mineral component as claimed in claim 21 .
[0018] It is also an object of the present invention to provide a method for preparing a hydraulic binder composition containing a carbonized mineral component.
[0019] This object is achieved by a method for producing a mineral binder according to claim 23 .
[0020] It is also an object of the present invention to provide a concrete composition having high strength and a low carbon footprint.
[0021] This object is achieved by a concrete composition according to claim 27 .
[0022] Further embodiments are protected by the respective dependent claims.
[0023] The present invention relates to a carbonized mineral component obtained from concrete waste and a preparation method thereof.
[0024] The carbonized mineral component has the lowest possible carbon footprint, and the concrete waste comprises one or more materials selected from concrete construction waste, recycled cement paste, concrete fines, dry concrete sludge, etc., which are treated by the specific method described in the present invention. The concrete waste is in the form of dry solids, i.e., powder in the case of concrete fines or dry concrete sludge, or composed of elements with a size of several centimeters in the case of concrete construction waste.
[0025] Concrete waste may have become partially carbonized due to exposure to air during use, which is particularly true for concrete construction waste.
[0026] The carbonization of concrete construction waste and its use in cementitious composites is well documented, both from a production and product perspective, and is the subject of numerous patent applications. Concrete waste can sequester CO2 through CO2 mineralization, and the use of carbonized concrete waste in cement and concrete composites offers the dual advantages of utilizing waste and sequestering CO2.
[0027] One limitation of using carbonated concrete waste is that its behavior is similar to or slightly better than that of limestone filler in cement and concrete composites, i.e., it does not have any pozzolanic reactivity that helps increase the ultimate strength of such concrete composites.
[0028] According to the present invention, it has been found that low-temperature heat treatment of carbonated concrete waste can produce a material with pozzolanic reactivity, and thus the carbonated concrete waste can be used as a mineral component in cement and concrete composites.
[0029] The method according to the present invention may include at least two steps.
[0030] One of the steps is a heating step, in which the concrete waste is heated to a temperature of 250°C - 600°C.
[0031] This heating step can be achieved in various ways using a low-temperature heat exchanger.
[0032] The energy used for the heat exchanger is preferably sustainable energy. This energy can come from the combustion of biomethane, the gas produced by the pyrolysis of renewable raw materials, hydrogen produced by the electrolysis of water (preferably the electrical energy produced by sustainable energy such as solar energy, wind energy, or water energy), or the electrical energy produced by the above sustainable energy. Further, the heat from other industrial processes can also be used, such as the heat from a cement kiln.
[0033] Preferably, before the heating step, the concrete waste is ground to at least 2000 cm 2 / g Blaine fineness, preferably 4000 cm 2 / g Blaine fineness, measured according to the method described in Standard EN 196-6:2018. The energy used for grinding is preferably the sustainable electrical energy described above.
[0034] The heating of the concrete waste can be achieved in a high-temperature gas flow heat exchanger. For example, a vertical countercurrent heat exchanger, a fluidized bed heat exchanger, or any other device suitable for transferring heat from a hot gas stream to a powdery material. A radiation heater or a heating screw conveyor can also be selected. Further, heating by directly mixing with hot clinker is also an option.
[0035] Specifically, the heating is carried out at a temperature T°C where 250°C < T°C < 800°C, preferably 250°C < T°C < 650°C, more preferably 300°C < T°C < 600°C.
[0036] Alternatively, such a heat exchanger can be arranged in parallel with a cement kiln or other industrial heat source, so as to exchange heat from the cement kiln to the heat exchanger by radiation, convection, and conduction.
[0037] The second step is a carbonation step, which is carried out at a certain moment in the production process.
[0038] Carbonization can be achieved with CO2, which comes from cement kilns (limestone decarbonization and fuel combustion), from the combustion of biomethane, from gases produced by pyrolysis of renewable raw materials, especially from the energy of the heating step or from other industrial processes or from ambient air.
[0039] A carbonization step, for example, performed after or during the grinding step, or before or during heating, can optimize the mechanical properties of the final binder.
[0040] The carbonization step is preferably performed before the heating step.
[0041] The carbonization step may in particular take place during the grinding step, or just after the grinding step.
[0042] Further, the carbonization step can be carried out before, during or after the heating step of the concrete waste. The two steps (carbonization and thermal activation) can be carried out separately in any order, or simultaneously.
[0043] Wet carbonization is defined in the present invention as carbonization in the presence of water or steam, the water content of which is at least 5% by weight, based on the total weight of the dry raw material to be carbonized. This can be achieved by injecting water or steam during the grinding stage. Further, it can be achieved during heating, especially at the initial stage or the end stage of heating, by injecting water or steam or saturated steam.
[0044] Wet carbonization of the ground material followed by heat activation provides the best strength increase.
[0045] However, dry carbonization at high temperatures, ie above 300°C, especially above 500°C, and especially above 700°C (carbonization of CaO, CaO from CSH and Ca(OH)2 decomposed by thermal activation) also inevitably produces such a result.
[0046] In fact, this step is accompanied by the injection of CO2, the amount of which is at least 5% by volume of the total gas volume during the carbonization process, preferably more than 15% by volume. Further, the wet carbonization can be carried out in an autoclave under high pressure using saturated steam and CO2-containing gas. The powdered material can be stirred during the high-pressure steam treatment. Since agglomeration may occur during the steam and carbonization treatment, the material can be depolymerized after the high-pressure steam treatment.
[0047] Dry carbonization is defined in the present invention as carbonization at a moisture content of less than 5% by weight of the total weight of the dry raw material to be carbonized.Dry carbonization can be carried out during the described stages of the method.
[0048] The average particle size of the concrete waste is preferably 0.005-5 mm. It has been found that using smaller sized concrete waste particles can improve the performance and the properties of the resulting mineral composition.
[0049] Concrete waste either consists entirely of hardened cement paste (cement and water) or is a mixture of hardened cement paste and partly ground sand or aggregate. Preferably, concrete waste contains at least 10% by weight of hardened cement paste.
[0050] The mineral component (MIC) obtained can be used as a binder (100%), for example for the production of geopolymers.
[0051] However, it is advantageous to use the obtained mineral component to partially replace the Portland cement in the binder composition. For example, in the binder composition, at least 25% to 75% by weight of the Portland cement can be replaced by the respective MIC according to the present invention.
[0052] With the present invention, not only can concrete waste be simply reactivated by heating to several hundred degrees Celsius as in the prior art, but the addition of a specific carbonization step at a given point in the manufacturing process can produce a new reinforced material.
[0053] According to the invention, the combination of carbonization of concrete waste and its heating to a temperature range produces a synergistic effect and produces a novel binder of unexpectedly high mechanical strength.
[0054] It was further found that grinding concrete waste to 2000cm 2 / g Blaine fineness and above, especially 4000cm 2 / g Blaine fineness, which is particularly beneficial for carbonized grades. Blaine fineness is measured as described in standard EN 196-6:2018.
[0055] As mentioned previously, this carbonization step can occur: - during or immediately following the grinding step, or — before or during the heating step.
[0056] Using the present invention, you can: - Producing a new MIC by reusing a large amount of concrete waste, — Significant gains due to CO2 absorption, — industrial-scale capture of CO2 from minerals, and — Improvement of the overall carbon footprint (reaction with CO2 + possible application of sustainable energy sources, so a possible 100% renewable energy mix).
[0057] Surprisingly, adding a carbonation step of the concrete waste before (or during) the heating step enables the final (reactivated) binder to have better reactivity (than after a simple heating step).
[0058] Adding the carbonation step can also improve the water demand (the reactivated slurry seems to require more water than the reference slurry).
[0059] According to a first aspect, the present invention relates to a method for preparing a carbonated mineral component, which is particularly used as a substitute for cement in a hydraulic binder composition, wherein a first raw material is carbonated and heat-treated, and the first raw material comprises at least one selected from concrete construction waste, recycled cement slurry, hardened concrete slurry, hardened cement slurry, concrete fines, dry concrete sludge, or any mineral component containing calcium silicate hydrate or calcium aluminate.
[0060] In one embodiment, the concrete waste either consists entirely of hardened cement slurry (cement and water) or is a mixture of hardened cement slurry and partially ground sand or aggregate. Preferably, the concrete waste contains at least 10% by weight of hardened cement slurry.
[0061] In one embodiment, the carbonation step is carried out before the heating step.
[0062] In one embodiment, the raw material is heated to a temperature T℃ where 250℃ < T℃ < 800℃, preferably 250℃ < T℃ < 650℃, more preferably 300℃ < T℃ < 600℃.
[0063] In one embodiment, the raw material is crushed to a fineness of 0.1 - 5 mm.
[0064] In one embodiment, the crushed raw material is ground to at least 2000 cm 2 / g Blaine fineness, preferably more than 3000 cm 2 / g Blaine fineness, more preferably 4000 cm 2 / g Blaine fineness or higher. In any case, the fineness of the crushed raw material is less than 15000 cm 2 / g Blaine fineness, and the fineness is measured according to the method described in Standard EN 196 - 6:2018.
[0065] In one embodiment, the raw material is heated in a heat exchanger, such as a gas - flow heat exchanger or a thermal screw conveyor, or by direct mixing with hot clinker.
[0066] In one embodiment, the raw material is heated in a vertical counter - current heat exchanger or a fluidized - bed heat exchanger or any other device suitable for transferring heat from a gas stream to a powdery material.
[0067] In one embodiment, the energy used by the heat exchanger is a sustainable energy source.
[0068] In one embodiment, the energy source is one or more of the following: combustion of biogas, gas produced by pyrolysis of renewable raw materials, hydrogen produced by water electrolysis, or electricity produced by solar energy, wind energy, or hydropower.
[0069] In one embodiment, heat from other industrial processes is used, such as a cement kiln or cement clinker cooler.
[0070] In one embodiment, carbonization is achieved with CO2 from limestone decarbonization and cement kilns from fuel combustion, from the combustion of biogas, from gases from pyrolysis of renewable raw materials, from the combustion of energy sources for the heating step or from other industrial processes or from ambient air.
[0071] In one embodiment, carbonization is performed after or during the grinding step, or before or during heating.
[0072] In one embodiment, carbonization is performed before, during or after the heating step of the feedstock.
[0073] In one embodiment, carbonization and heating of the feedstock are performed separately or simultaneously in any order.
[0074] In one embodiment, the carbonization is wet carbonization of the feedstock followed by heating.
[0075] In one embodiment, dry carbonization is the carbonization of CaO at a high temperature above 300° C., especially above 500° C., especially above 700° C., wherein the CaO comes from the thermally activated decomposed CSH and Ca(OH) 2 or other Ca-rich phases.
[0076] In one embodiment, wet carbonization is carbonization performed in the presence of water or steam, with a water content of at least 5% by volume.
[0077] In one embodiment, wet carbonization is achieved by one or more of the following: injecting water or steam during the grinding stage, injecting water or steam or saturated steam during heating, especially at the beginning or end of heating.
[0078] In one embodiment, the wet carbonization further comprises supplying or injecting CO2 in an amount of at least 10 volume %, preferably more than 20 volume %, based on the total gas volume during carbonization.
[0079] In one embodiment, wet carbonization is carried out in an autoclave using saturated steam and a high pressure gas containing CO2.
[0080] In one embodiment, the powdered material may be agitated during the autoclave treatment, and since agglomeration may occur during the steam and carbonization treatments, the material may be deagglomerated after the autoclave treatment.
[0081] In one embodiment, dry carbonization is carbonization at a moisture content of less than 5% by weight based on the total weight of the dry raw material to be carbonized.
[0082] Another aspect of the present invention relates to a carbonized mineral component prepared according to one or more of the above embodiments, wherein the carbonized mineral component comprises a ground first raw material that is carbonized and heated, and includes at least one selected from concrete construction waste, hardened concrete slurry, hardened cement slurry, or any mineral component containing hydrated calcium silicate and calcium aluminate.
[0083] In one embodiment, the mineral component has a Blaine fineness of 2000 cm 2 / g-10000cm 2 / g, preferably 3000cm 2 / g-700cm 2 / g, measured according to the method described in standard EN 196-6:2018.
[0084] Another aspect of the present invention also relates to a method for producing a hydraulic binder, wherein a carbonized mineral component according to one or more of the above embodiments or a carbonized mineral component produced by a method according to one or more of the above embodiments is mixed with at least one cement component, in particular Portland cement or Portland cement clinker.
[0085] In one embodiment, the carbonized mineral component is added to the cement clinker before or during grinding and ground together with the cement clinker to obtain a binder composition comprising at least the carbonized mineral component and cement.
[0086] In one embodiment, the ground carbonized mineral component replaces the cement component in the mixture in an amount of 25-75% by weight.
[0087] Another aspect of the present invention also relates to the use of the carbonized mineral component according to one or more of the above embodiments or the carbonized mineral component prepared according to one or more of the above embodiments as a cement substitute in a hydraulic binder composition for mortar and concrete.
[0088] Another aspect of the present invention also relates to a hydraulic binder composition for mortar and concrete, comprising a carbonized mineral component according to the above embodiment or a carbonized mineral component prepared by the method according to one or more embodiments and a cement component, in particular Portland cement or Portland cement clinker. BRIEF DESCRIPTION OF THE DRAWINGS
[0089] The present invention will be explained by way of examples and drawings. In the drawings:
[0090] Figure 1 It is a process flow diagram;
[0091] Figure 2 It is a suitable device for heating raw materials;
[0092] Figure 3 is another process flow diagram;
[0093] Figure 4 is the compressive strength of the comparative example at 2, 7 and 28 days, wherein the concrete construction waste replaces 25% of the cement and the calcination temperature is 450°C;
[0094] Figure 5 is the compressive strength of the comparative example at 2, 7 and 28 days, wherein the concrete construction waste replaces 25% of the cement and the calcination temperature is 600°C;
[0095] Figure 6 is the compressive strength of the comparative example at 2, 7 and 28 days, wherein the recycled concrete fines replace 25% of the cement and the calcination temperature is 450°C;
[0096] Figure 7 is the compressive strength of the comparative example at 2, 7 and 28 days, wherein the recycled concrete fines replace 25% of the cement and the calcination temperature is 600°C;
[0097] Figure 8 is the compressive strength of the comparative example at 2, 7 and 28 days, in which the concrete sludge replaces 25% of the cement and the calcination temperature is 550°C;
[0098] Fig. 9 is the compressive strength of CEM I 52,5N after 28 days, compared with examples of recycled cement slurry, calcined recycled cement slurry and carbonized and calcined recycled cement slurry with 25% replacement of cement, calcination temperature 450°C.
[0099] Fig.10 is the compressive strength of CEM I 52,5N after 28 days, compared with examples of recycled cement slurry, calcined recycled cement slurry and carbonized and calcined recycled cement slurry with 50% replacement of cement, calcination temperature 450°C. DETAILED DESCRIPTION
[0100] The method according to the invention comprises two essential process steps.
[0101] One essential step is heating the first raw material, wherein the raw material may include one or more selected from concrete construction waste, hardened concrete slurry, hardened cement slurry, or any mineral component containing hydrated calcium silicate, calcium aluminate, and the like.
[0102] The purpose of the heating step is to allow the thermal treatment of the first feedstock to produce a material having pozzolanic reactivity, and the heating step can therefore be considered an activation step.
[0103] The heating step can be carried out in any suitable device capable of transferring heat to a raw material consisting of particles, especially fine particles. The particles to be activated can be particles obtained by crushing the raw material. In this case, the particle size is preferably between 0.1 and 5 mm.
[0104] If necessary, the crushed material can be ground to a Blaine fineness of at least 2000 cm 2 / g, preferably more than 3000cm 2 / g, more preferably 4000cm 2 / g or higher, measured according to the method described in standard EN 196-6:2018.
[0105] To transfer heat into this material, one can use e.g. Figure 3 The device shown is a rotary drum heat exchanger.
[0106] Such a heat exchanger can be heated by means of electric heaters, for example, which are placed circumferentially on the outer wall of the rotary drum heat exchanger. Such a rotary heat exchanger is advantageous especially in the case of heating powdered materials.
[0107] In particular, the final ground material as described above may be heated in a fluidized bed apparatus in which hot gases are directed through the finely ground material.
[0108] The heating is carried out by heating the raw materials to a temperature of 250°C-650°C, preferably 400°C-600°C.
[0109] The energy required for heating the feedstock can be electrical energy or a stream of hot gas, wherein in both cases it is preferred that the heating be carried out using sustainable energy sources.
[0110] Sustainable energy in the case of electrical energy may be from solar energy, wind energy, hydro energy or similar energy sources.
[0111] Additionally, hot gas streams from other industrial processes may be used.
[0112] If the temperature range is in the corresponding region between 250°C and 650°C, these gas streams can be used directly, thus cooling the higher temperature gas. For example, these gas streams can be used directly by flowing through a fluidized bed, or indirectly by heating gaseous ambient air in a heat exchanger. The latter can occur, for example, if the gas stream contamination level is within the range of undesirable gradients in the product.
[0113] Examples of these gas streams may be hot gases from a cement rotary kiln or a cement clinker cooling plant.
[0114] In addition, the hot gas flow can be achieved by the combustion of flammable liquids or gases. Preferably, these flammable liquids or gases come from sustainable processes.
[0115] This could be, for example, hydrogen produced by electrolysis of water using sustainable electricity, combustion of biomethane or biogas such as methane produced by microbial recombination of hydrogen and CO2 from natural gas reservoirs, alcohol produced by fermentation of sustainable vegetable products or anaerobic respiration (paralysis) of sustainable vegetable products.
[0116] In addition to the first substantial step of volcanic ash activation by heating, a second substantial step is also carried out, namely the carbonization of the raw material.
[0117] Generally speaking, the carbonization can be carried out after or during the crushing and grinding of the concrete waste. Preferably, the carbonization step is carried out after the crushing and grinding of the concrete waste.
[0118] In case of using concrete sludge, crushing and grinding are not necessary.
[0119] Further, the carbonization may be wet carbonization or dry carbonization.
[0120] The definitions of wet carbonization and dry carbonization have been given above.
[0121] Generally, as mentioned above, carbonization can be carried out with a CO2-rich gas stream, which can be a separate gas stream containing CO2, CO2 from ambient air or from an industrial process, etc. Carbonization can also be achieved partially or completely by using a gas stream as heating.
[0122] If the carbonization is done during the heating step, this means, for example, that it is done at the beginning or at the end of the heating step, using the same apparatus.
[0123] In addition to the above apparatus, heating and carbonization can be carried out in an autoclave with steam or saturated steam, CO2-rich gas and heat.
[0124] After these two substantial steps, a depolymerization step may be performed if necessary.
[0125] The deagglomeration step may be a combined grinding and mixing step of the carbonized mineral component and cement clinker in a rotary mill according to the invention.
[0126] Figure 1 An embodiment for implementing the present invention is schematically shown.
[0127] After the raw materials are crushed, they are ground into a fineness of about 4000cm 2 / g, the fineness is determined according to the method described in standard EN 196-6:2018. At this stage, carbonization can be carried out, in which the grinding is carried out under a CO2-rich gas stream or a CO2-containing atmosphere.
[0128] Alternatively or further, a carbonization step may be performed afterwards, wherein the carbonization as described above may be performed in various ways in various devices, as long as the ground raw material is perfused with a CO2-rich gas stream. Thereafter, the crushed and / or ground raw material is heated at a temperature of 450° C. or 600° C. Alternatively or further, carbonization may even occur during the heating of the ground raw material.
[0129] After the heating step and cooling of the material obtained in this way, the carbonized mineral component produced in this way is mixed with Portland cement as a replacement for this cement component.
[0130] exist Figure 3 Two general process paths for embodiments of the present invention are shown in FIG. 1 , where in the first process carbonization occurs before heating but without milling, and milling occurs after the heating step.
[0131] In the second process, the raw material is first ground to 4000cm 2 / g, then carbonized and then heated.
[0132] Figure 4 and Figure 5 A comparative example is shown, in which a comparison is made on an example in which 25% of the Portland cement is replaced by concrete construction waste. The calcination temperature (if any) is Figure 4 At 450°C and Figure 5 The temperature is 600℃.
[0133] The dashed lines show the compressive strength of CEM I 52,5N after 2, 7 and 28 days.
[0134] From left to right, four situations are shown: concrete construction waste, carbonized concrete construction waste, calcined construction waste, and carbonized and calcined concrete construction waste.
[0135] It can be seen that the short-term compressive strength (2 days) of each sample is almost the same in both graphs. The same is true for the 7-day medium-term compressive strength. However, it is clear that the calcination of concrete construction waste gives a slightly higher strength, and carbonization and calcination further enhance the strength. In the comparison between the calcination temperatures, the higher the temperature of the carbonized and calcined concrete construction waste, the strength only slightly increases, while the strength of the other samples does not change at all.
[0136] The same situation also appears in the long-term compressive strength. On the one hand, both calcined and calcined and carbonized show an increase in strength.
[0137] On the other hand, higher calcination temperature slightly increased the compressive strength after 28 days.
[0138] exist Figure 6 and Figure 7 The graph in shows the effect of recycled concrete fines. Similarly, 25% of Portland cement was replaced and the calcination temperatures were 450°C and 600°C respectively.
[0139] In these samples, carbonization appears to have a greater effect on the short- and medium-term compressive strength than calcination temperature, which has only a slight increasing effect.
[0140] exist Figure 8 The samples in which Portland cement was replaced by 25% of concrete sludge, carbonized concrete sludge and carbonized and calcined concrete sludge were shown and compared. The calcination temperature was 550°C.
[0141] The results show that carbonization significantly enhances the medium- and long-term compressive strength. Carbonization and calcination further enhance the compressive strength.
[0142] Fig. 9 and Fig.10 The CEM I 52,5 sample is shown, as well as the sample with 25% ( Fig. 9 ) and 50%( Fig.10 ) of recycled cement slurry to replace cement. The calcination temperature in both cases was 450 °C.
[0143] As expected from the other samples, calcination resulted in higher 28-day compressive strength compared to the recycled cement paste. Carbonized and calcined recycled cement paste showed a greater increase in compressive strength.
[0144] The compressive strength is slightly lower at 50% replacement, but still very high.
[0145] The concrete construction waste used in these examples is partially carbonized because, throughout its life cycle, it is exposed to CO2 in the air. These examples show that the method of the present invention provides excellent performance even if the waste is partially carbonized before treatment according to the present invention.
[0146] The result is that, even without carbonization, heating the above-mentioned recycled cement slurry or other raw materials to a temperature of 250°C to 650°C will produce mineral components that can contribute to the 28-day compressive strength of the binder composition.
[0147] A further result is that the incorporation of CO2 by carbonization of the raw materials in a suitable manner to produce a carbonized mineral component contributes to the strength of the mineral component even when heated at relatively low temperatures (450°C) and further acts as a CO2 trap.
[0148] By using sustainable energy to heat the mineral component, the carbon footprint of the mineral component can be reduced to zero, and the overall carbon footprint of the binder composition having the mineral component and the cement component can be significantly reduced.
[0149] The raw materials are heated and carbonized in the manner described, absorb CO2 and act as a CO2 sink, and can be mixed with a cement component to form a hydraulic binder composition, making the carbon footprint of the entire binder composition zero.
Claims
1. A method for preparing an at least partially carbonized mineral component for use as a cement substitute in hydraulic binder compositions, characterized in that The raw materials are heated or carbonized and then heated, where the raw materials are heated to a temperature T℃ of 250℃ < T℃ < 800℃, preferably 250℃ < T℃ < 650℃, more preferably 300℃ < T℃ < 600℃, and the raw materials comprise at least one selected from the following components: - Concrete construction waste, - Recycled cement slurry, - Hardened concrete slurry, - Hardened cement slurry, - Concrete fines, - Dry concrete sludge, or - Any mineral component containing calcium silicate hydrate or calcium aluminate.
2. The method according to claim 1, characterized in that: The concrete waste consists entirely of hardened cement slurry or is a mixture of hardened cement slurry and partially ground sand or aggregate, and the concrete waste preferably contains at least 10% by weight of hardened cement slurry.
3. The method according to claim 1, characterized in that The carbonization step is carried out before, during, or after the heating step.
4. The method according to any one of the preceding claims, characterized in that The raw materials are crushed to a fineness of 0.1 - 5 mm.
5. The method according to any one of the preceding claims, characterized in that The crushed raw material is ground to a Blaine fineness of at least 2000 cm 2 / g, preferably more than 3000cm 2 / g, more preferably 4000cm 2 / g or higher, measured according to the method described in standard EN 196-6:2018.
6. A method according to any one of the preceding claims, characterised in that The raw materials or carbonized raw materials are heated in a heat exchanger, such as a gas flow heat exchanger or a thermal screw conveyor, or by direct mixing with hot clinker.
7. A method according to any one of the preceding claims, characterised in that The raw materials or carbonized raw materials are heated in a vertical countercurrent heat exchanger or a fluidized bed heat exchanger or any other device suitable for transferring heat from a gas stream to a powdered raw material.
8. The method according to any one of the preceding claims, characterized in that The energy used in the heat exchanger is sustainable energy.
9. The method according to any one of the preceding claims, characterized in that The energy is sourced from one or more of the following: - Combustion of biogas, - Gas generated from pyrolysis of renewable raw materials, - Hydrogen generated from electrolysis of water, or - Solar thermal energy generated by a solar furnace, - Electrical energy generated from solar, wind, or water energy.
10. The method according to any one of the preceding claims 1 to 8, characterized in that Heat generated using other industrial processes, such as a cement kiln, is used.
11. The method according to any one of the preceding claims, characterized in that The carbonization is achieved using CO2, which comes from decarbonization of limestone and fuel combustion in a cement kiln, combustion of biogas, gas generated from pyrolysis of renewable raw materials, etc., combustion of the energy source in the heating step, other industrial processes, or ambient air.
12. The method according to any one of the preceding claims, characterized in that Carbonization is carried out during or after the grinding step, or before or during heating.
13. A method according to any one of the preceding claims, characterised in that Carbonization is wet carbonization of the raw materials followed by heating.
14. A method according to any one of the preceding claims, characterised in that Dry carbonization is the carbonization of CaO at a temperature above 300℃, especially above 500℃, and especially above 700℃, where the CaO comes from calcium silicate hydrate and Ca(OH)2 decomposed by thermal activation and other Ca-rich phases.
15. A method according to any one of the preceding claims, characterised in that Carbonization is wet carbonization carried out in the presence of water or steam, and the water content is at least 5% by weight based on the total weight of the dry raw materials to be carbonized.
16. A method according to any one of the preceding claims, characterised in that Wet carbonization includes one or more of the following: injecting water or steam during the grinding stage, injecting water or steam or saturated steam during heating, especially during the initial or final stage of heating.
17. A method according to any one of the preceding claims, characterised in that Wet carbonization also includes injecting CO2, and the amount of CO2 injected is at least 10% by volume, preferably more than 20% by volume, based on the total gas volume during carbonization.
18. A method according to any one of the preceding claims, characterised in that Wet carbonization is carried out in an autoclave using saturated steam and high-pressure gas containing CO2.
19. The method according to any one of the preceding claims, characterized in that The powdered raw materials are stirred during high-pressure steam treatment, and the powdered materials are depolymerized after high-pressure steam treatment.
20. The method according to any one of claims 1 to 14 and 16 to 19, characterized in that Dry carbonization is carried out at a humidity of less than 5% by weight based on the total weight of the dry raw materials to be carbonized.
21. A carbonized mineral component prepared by the method according to any one of the preceding claims.
22. The carbonized mineral component according to claim 21, characterized in that The Blaine fineness of the carbide mineral component is 2000 cm 2 / g-10000cm 2 / g, preferably 3000-7000cm 2 / g, measured according to the method described in standard EN 196-6:2018.
23. A method for preparing a hydraulic binder composition, characterized in that: The carbonized mineral component according to claim 21 or 22 or the mineral component obtained by the method according to any one of claims 1 to 20 is mixed with at least one cement component, in particular Portland cement cement or Portland cement cement clinker.
24. The method according to claim 23, characterized in that The carbonized mineral component is added to the cement clinker before or during grinding and ground together with the cement clinker to obtain a binder composition comprising at least the carbonized mineral component and the cement clinker.
25. The method according to claim 23 or 24, characterized in that The hydraulic binder composition comprises a ground carbide mineral component in an amount of 25% to 75% by weight of the hydraulic binder composition.
26. Use of a carbonized mineral component according to claim 21 or 22 or a carbonized mineral component obtained according to any one of claims 1 to 20 as a cement substitute in a hydraulic binder composition for mortar and concrete.
27. A hydraulic binder composition for mortar and concrete, comprising the carbonized mineral component according to claim 21 or 22 or the carbonized mineral component obtained by the method according to any one of claims 1 to 20 and a cement component, preferably Portland cement or Portland cement clinker.
28. A concrete composition comprising the hydraulic binder composition according to claim 27 and aggregate.
Citation Information
Patent Citations
Use of carbonated recycled concrete fines as supplementary cementitious material
EP3498681A1
Method using recycled concrete fines for co2 / sox removal from exhaust gas
EP3581257A1
Use of carbon dioxide from and for cement
EP3656750A2
Cement composition using waste concrete fine powder and method of preparing the same
JP2005320202A
Method for simultaneous exhaust gas cleaning and manufacturing of supplementary cementitious material
WO2019115722A1